Editorial: a paradigm shift in NUDT15 assessment—towards predictive and personalised medicine in Crohn's disease? Authors' reply. Issue 6 (4th March 2022) - Kim, Eun Sil; Kang, Ben
LINKED CONTENT: This article is linked to Kim et al papers. To view these articles, visit https://doi.org/10.1111/apt.16769 and https://doi.org/10.1111/apt.16798